2005
DOI: 10.1021/jp0460588
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Computational and Experimental Study of the Hydrogen-Bonded Dimers of Xanthine and Hypoxanthine

Abstract: In addition to uracil, the noncanonical nucleobases xanthine and hypoxanthine are important lesions that are formed from the canonical bases when a cell is under oxidative stress. It is known that they lead to point mutations; however, more detailed information about their ability to form hydrogen-bonded complexes is not available. In the present paper such information is obtained by a combined experimental and theoretical approach. Accurate association constants of xanthosine and inosine dimers are determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…[61] Previous computational studies employed an approach suggested by Williams et al, which considers the transition to the fluid as a two-step process by first condensing the gaseous compound to a pure liquid and subsequently diluting the pure liquid to the 1 m standard state. [62][63][64] This procedure should, in principle, give more accurate results concerning entropy changes in solution and comparison with experimental data, but we refrain from using this approach because our aim is to predict entropy changes from pure theory. The method of Williams et al requires knowledge of macroscopic quantities, for example, the condensation entropy, that are not available in the single-molecule picture.…”
Section: Guestmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] Previous computational studies employed an approach suggested by Williams et al, which considers the transition to the fluid as a two-step process by first condensing the gaseous compound to a pure liquid and subsequently diluting the pure liquid to the 1 m standard state. [62][63][64] This procedure should, in principle, give more accurate results concerning entropy changes in solution and comparison with experimental data, but we refrain from using this approach because our aim is to predict entropy changes from pure theory. The method of Williams et al requires knowledge of macroscopic quantities, for example, the condensation entropy, that are not available in the single-molecule picture.…”
Section: Guestmentioning
confidence: 99%
“…This means that even in calculations employing continuum solvation models such as COSMO, the translational and rotational entropy contributions for the gas phase are employed, which do not accurately reflect the conditions in the condensed phase due to solvent–solute interactions and a clearly reduced free volume of translation in the fluid 61. Previous computational studies employed an approach suggested by Williams et al., which considers the transition to the fluid as a two‐step process by first condensing the gaseous compound to a pure liquid and subsequently diluting the pure liquid to the 1 M standard state 6264. This procedure should, in principle, give more accurate results concerning entropy changes in solution and comparison with experimental data, but we refrain from using this approach because our aim is to predict entropy changes from pure theory.…”
Section: Theoretical Detailsmentioning
confidence: 99%
“…The formation of amide and imide dimers is frequently studied by NMR or IR spectroscopy to determine self-association constants in solution. 7 , 8 Rebek and co-workers 9 examined the intramolecular imide–imide and amide–amide association through NMR measurements. The corresponding results indicate that despite their lower acidity, amides exhibit stronger self-associations than imides.…”
Section: Introductionmentioning
confidence: 99%
“…Computational chemistry can play an important role in understanding the binding interactions between HYP and the natural nucleobases since information about discrete interactions can be more readily obtained compared with experiment. Indeed, computational studies of the hydrogen-bonding ability, 36,37 as well as other molecular properties, [38][39][40][41][42][43][44][45] of hypoxanthine have recently appeared in the literature. However, information about stacking interactions involving hypoxanthine has yet to be obtained.…”
Section: Introductionmentioning
confidence: 99%